Cosmetics utilization and associated adverse events: A community based cross-sectional study - Sweta Kumari; Biplab Pal; Devesh Tewari; Sanjeev Kumar Sahu (Elsevier, 2023)
Background: Cosmetics can enhance a person's perception of their beauty, but they can also be harmful. Despite a high incidence of adverse events, no study was conducted on cosmetics usage patterns and their associated adverse events at the community level in India. Methodology: A cross-sectional study was conducted among the 400 general population in the Jalandhar, Amritsar, and Ludhiana regions of Punjab, India. The study was conducted from May 2021-September 2022. Data collection was done by using a validated questionnaire. Descriptive statistics were used to summarize proportions, and logistic regression was used to identify the predictors of cosmetics-related adverse events. Results: A total of 400 respondents participated in the study. More than half of the participants (54.7%) used 1-2 cosmetics per day, with nearly fifty percent (n = 49%) reportedly using them twice daily. The most commonly used cosmetics products were makeup (35.9%), followed by personal care products (28%). A total of 132 users reported adverse events due to cosmetics. The prevalence of cosmetic-induced adverse events was found to be 33%. The most commonly reported adverse events were itching (n = 58), redness (n = 59), and pimples (n = 42). The majority of reported adverse events were related to skin care products (46%), hair care 39 (28.1%), and personal care products 24(17.3%). Conclusion: The prevalence of adverse events among cosmetics users were found to be high. There is an urgent need to create awareness of the rational use of cosmetics among users. Additionally, the establishment of a cosmetovigilance center is also recommended.